ANALISIS PERBANDINGAN BAHASA MANUSIA DAN SISTEM KOMUNIKASI PADA BINATANG: KAJIAN TEORI DAN SEJARAH - Aurora Karina Tomia Putri; Diana Pangestuti; Marsya; Dr. Drs. Eko Kuntarto, M. Pd. M.Comp.Eng; Muhammad Sholeh, S.Pd., M.Pd. (STKIP Subang, 2024)
This research compares human language and animal communication systems through theoretical and historical approaches. Human language as a complex communication system includes syntax, semantics, and pragmatics, which allow abstraction and flexibility of meaning, while animal communication is more limited to direct context with denotative cues. Using the literature study method, it is found that human language has unique capabilities in abstraction, symbolization, and recursivity, which do not exist in animal communication systems. Through the analysis of comparative linguistics and communication ethology, this research reveals fundamental differences in the structure and function of communication across species. Keywords: human language, animal communication, species communication systems